Characterization of the proteins of bacterial strain isolated from contaminated site involved in heavy metal resistance - a proteomic approach - Bar, Chinmayee; Patil, Rajendra; Doshi, Jignesh; Kulkarni, Mahesh J.; Gade, Wasudeo N. (Journal of Biotechnology, 2007)
The present study describes response of a bacterial strain isolated from a polluted river to heavy metal toxicity. The bacterium was identified to be Klebsiella pneumoniae by biochemical tests using API 20E strips and 16S ribotyping. The isolate was studied for its tolerance to two heavy metals, i.e., cobalt (Co2+) and lead (Pb2+) by growing it in citrate mineral medium (CMM). Proteomic approach involving two-dimensional polyacrylamide gel electrophoresis (2D PAGE) and mass spectrometry (MS) was used to identify the differentially expressed proteins under heavy metal stress. Two of the differentially expressed proteins were identified to be L-isoaspartate protein carboxymethyltransferase type II and DNA gyrase A. To our knowledge, this is for the first time that K pneumoniae has been reported to be present in metal contaminated site and L-isoaspartate protein carboxymethyltransferase type II protein to be over expressed under heavy metal stress. The role of these proteins in metal tolerance is discussed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 2D PAGE; heavy metal toxicity; Mass spectrometry